2002
DOI: 10.1093/humrep/17.8.2134
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of non-disjunction in human female meiosis: the co-existence of two modes of malsegregation evidenced by the karyotyping of 1397 in-vitro unfertilized oocytes

Abstract: The implication of both chromosome and chromatid abnormalities in the occurrence of non-disjunction are discussed in relation to the recent data on chromatid cohesion throughout cell division. The results were consistent with the hypothesis of an unequal occurrence of non-disjunction among the chromosome groups in female meiosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
70
1
12

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 85 publications
21
70
1
12
Order By: Relevance
“…First polar body screening is the only pre-implantation and, more precisely, preconception screening technique allowed by French legislation for recurrent implantation failure, though analysis of the complete cohort, fertilized and unfertilized oocytes, is possible. However, due to time limitations only 76% of first polar bodies could be assessed by FISH, a proportion similar to published values (81.6% [35], 85.5% [4]), but much higher than successful oocyte karyotyping rates (less than 50% of unfertilized oocytes [36]). …”
Section: Discussionsupporting
confidence: 79%
“…First polar body screening is the only pre-implantation and, more precisely, preconception screening technique allowed by French legislation for recurrent implantation failure, though analysis of the complete cohort, fertilized and unfertilized oocytes, is possible. However, due to time limitations only 76% of first polar bodies could be assessed by FISH, a proportion similar to published values (81.6% [35], 85.5% [4]), but much higher than successful oocyte karyotyping rates (less than 50% of unfertilized oocytes [36]). …”
Section: Discussionsupporting
confidence: 79%
“…Even if the sample size was too small to allow assessment of aneuploidy after this procedure, no chromosome break was observed in any oocyte group. A large proportion of the oocytes was not interpretable (22/48, 46%) or lost (12/48, 25%), in accordance with a previous study using Tarkowski's method, where the best success rate of karyotyping unfertilised oocytes was 45.9% [45].…”
Section: Discussionsupporting
confidence: 88%
“…Current data suggest an aneuploidy rate of 20.8% ( 24,31 and unpublished data), double the rate found by karyotyping ( 22 ). Chromosome loss and gain occurred almost equally in the oocyte and 1 st PB in the abnormal samples, in accordance with the theoretical expectations of the outcome of primary meiotic non-disjunction of the two homologs.…”
Section: The Aneuploidy Rate In Human Oocytessupporting
confidence: 62%
“…Recent karyotyping data that includes chromatid anomalies and the more specific FISH analyses indicated that the overall rate of chromosome and chromatid imbalance in human oocytes is about 11% for women of maternal age 32-34 years ( 15,17,22,35 ). However, several independent studies of aneuploidy in MII oocytes and corresponding 1 st PBs have used CGH to obtain exact information on all chromosomes.…”
Section: The Aneuploidy Rate In Human Oocytesmentioning
confidence: 99%